ANALISIS PENGARUH KUALITAS PELAYANAN DAN WAKTU TUNGGU TERHADAP LOYALITAS PASIEN YANG DIMEDIASI OLEH KEPUASAN PASIEN (STUDI EMPIRIS PASIEN DI IGD RS St. CAROLUS BORROMEUS) - Yustina Tantriwulan Kusumawardhani; Muchlis Mas’ud; Lembah Adriani (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to analyze the effect of service quality and waiting time on patient loyalty mediated by patient satisfaction in the ER of St. Carolus Borromeus Hospital. Methods: This study used a quantitative design with a cross-sectional approach. The sample consisted of 82 emergency department (ED) patient respondents selected using a purposive sampling technique. Data were collected through a structured questionnaire and analyzed using Partial Least Square–Structural Equation Modeling (PLS-SEM) to test the direct and indirect relationships between variables. The results showed that service quality and waiting time had a positive and significant effect on patient satisfaction. In addition, service quality, waiting time, and patient satisfaction also had a positive and significant effect on patient loyalty. Patient satisfaction was proven to mediate the influence of service quality and waiting time on patient loyalty. Discussion: The findings of this study emphasize the importance of improving service quality and effective wait time management in increasing patient satisfaction and loyalty in the emergency department (ED). Patient satisfaction plays a key role in shaping patient loyalty and therefore needs to be a primary focus in hospital service quality improvement strategies